Topical, systemic and biologic therapies in hidradenitis suppurativa: pathogenic insights by examining therapeutic mechanisms - John W. Frew; Jason E. Hawkes; James G. Krueger (SAGE Publishing, 2019)
Hidradenitis suppurativa (HS) is a chronic inflammatory disease of the skin, manifesting in chronic, recurrent painful pustules, nodules, boils and purulent draining abscesses. Our current understanding of the pathogenesis of the disease is incomplete. This review aims to identify available treatment options in HS and discuss the pharmacological mechanisms through which such agents function. Identifying common pathways may inform our understanding of the pathogenesis of HS as well as identify future therapeutic targets. The pharmacological mechanisms implicated in topical therapies, antibiotic, hormonal, systemic immunomodulatory and biologic therapies for HS are discussed. Significant differences exist between agents and implicated pathways in therapy for mild and severe disease. This is an expression of the possible dichotomy in inflammatory pathways (and treatment responses) in HS. Studies involving monoclonal antibodies provide the greatest insight into what these specific mechanisms may be. Their variable levels of clinical efficacy compared with placebo bolsters the suggestion that differential inflammatory pathways may be involved in different presentations and severity of disease. Nuclear factor kappa B (NF-κB), tumor necrosis factor (TNF)-α and other innate immune mechanisms are strongly represented in treatments which are effective in mild to moderate disease in the absence of scarring or draining fistulae, however complex feed-forward mechanisms in severe disease respond to interleukin (IL)-1 inhibition but are less likely to respond to innate immune inhibition (through NF-κB or TNF-α) alone. It is unclear whether IL-17 inhibition will parallel TNF-α or IL-1 inhibition in effect, however it is plausible that small molecule targets (Janus kinase1 and phosphodiesterase 4) may provide effective new strategies for treatment of HS.